Significant role of long non-coding RNA MALAT1 in deep vein thrombosis via the regulation of vascular endothelial cell physiology through the microRNA-383-5p/BCL2L11 axis. Issue 5 (2nd May 2022) - Wang, Hecheng; Lin, Shusen; Yang, Yujie; Zhao, Mingyu; Li, Xichun; Zhang, Lanli
ABSTRACT: Deep vein thrombosis (DVT) is a vascular disease. The long non-coding RNA (lncRNA), metastasis-associated lung adenocarcinoma transcript 1 (MALAT1), is positively expressed in DVT tissues, and regulates the biological behavior of endothelial progenitor cells. Here, we explored whether MALAT1 affected the physiology of human vascular endothelial cells (HUVECs) and analyzed its underlying mechanism. To overexpress/silence the expression of MALAT1 in HUVECs, MALAT1-plasmid/MALAT1-small interfering RNA (siRNA) was used. The 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide and flow cytometry analyses were performed to observe the cell viability and apoptosis. Reverse transcription-quantitative polymerase chain reaction and western blotting were used to determine the apoptosis-related protein and gene expression levels. We used Starbase software to predict the associations among MALAT1, microRNA (miR)-383-5p, and BCL2-like 11 (BCL2L11). Luciferase reporter assay was used to validate their relationship. Compared to the control vector group, MALAT1-plasmid suppressed the viability and induced apoptosis of HUVECs, while improving Bcl-2-associated X protein (Bax) expression and decreasing Bcl-2 expression. There was an interaction between MALAT1 and miR-383-5p. Compared to the control siRNA group, MALAT1-siRNA increased the cell viability, reduced cell apoptosis, upregulated Bcl-2 expression, and suppressed Bax expression. These changes were reversed by the miR-383-5p inhibitor. Additionally, we verified that BCL2L11 is a target of miR-383-5p. miR-383-5p improved the cell proliferation, while decreasing cell apoptosis in HUVECs by targeting BCL2L11. Therefore, the lncRNA-MALAT1/miR-383-5p/BCL2L11 axis may be effective for DVT treatment. Graphical Abstract: uf0001